Developing Values of Pancasila’s Second Principle for Sixth Grader Students - Muhammad Abduh; Tukiran Taniredja (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
The research objective was to determine (1) the development of values from the second principle of Pancasila for sixth graders; (2) what are the constraints of sixth grade teachers in developing the values of the second principle of Pancasila; (3) the solution from teachers to overcome the obstacles in developing the values to the learners. Data were collected using an open questionnaire. Informants were the teachers of sixth graders. Data were analyzed using data reduction, data display, and conclusion/ verification. To develop the values of the second principle of Pancasila: (a) students needed the examples from various stakeholders such as teachers, parents and community leaders; (b) the problem is the selfish attitude of learners who did not cooperate with their friends; (c) the solution suggested were having patience and diligence.